PENGARUH PERBANDINGAN KINERJA SOLAR STILL MENGGUNAKAN COVER PIRAMIDA DAN PENAMBAHAN RUANG KONDENSASI - Dias Mardianto; Nova Risdiyanto Ismail Ismail; Akhmad Farid; Purbo Suwandono (Scientific Journal of Mechanical Engineering Kinematika, 2024)
One-third of Indonesia's territory is ocean, but Indonesia still experiences difficulties in clean water, especially in coastal areas. Solar still technology can be used to overcome these problems. There have been many studies conducted to improve the performance of solar stills, one of which is to change the shape of the cover or cover. The purpose of this study was to compare the effect of pyramid cover with the addition of condensation chamber (WES). This research uses experimental and theoretical methods. This study used fin absorbent plates using mortar material. The result of this study is the highest solar still performance using the WES cover compared to using the pyramid cover experimentally and theoretically. The highest productivity using WES cover is 2,087 kg / day for experiments and for theoretical values of 2,287 kg / day, while the efficiency obtained is 31.66% for experiments and 32,19% for theoretical. The difference in freshwater productivity and solar still efficiency between experimental and theoretical was not significant.